(untitled) (International Journal of Agriculture and Sustainable Development, 2023)
A tree stands as an abstract example of a basic form of life. It helps in greening cities and contributing to the preservation of natural resources and climate. It’s a boon to the economy and creates jobs, too. When checking the health of a tree, most methods are either intrusive or even destructive. Non-destructive infrared thermography (IRT) has proven useful for inspecting trees and wood for damage and voids that could weaken the material’s strength and longevity. In this paper, we summaries previous research on using IRT to assess tree health. It’s set against the backdrop of the role trees play in maintaining ecological harmony and the various methods available for spotting signs of tree decline. These differences are highlighted, along with the main factors that have been shown to disrupt the trees’ thermal pattern when applied to wood or trees. As with other non-destructive methods, the IRT does not differentiate between the various forms of damage or the agents responsible for them. However, it does allow for differentiation between normal and unhealthy tissue. As evidenced by its demonstrated effectiveness, rapidity, low cost, and longevity, the technology holds great promise.